Techno-economic analysis of a cost-effective power generation system for off-grid island communities : a case study of Gilutongan Island, Cordova, Cebu, Philippines - Lozano, Lorafe (2021)
Off-grid, rural island communities seldom have access to electricity and for those that do, the quality and availability are unsatisfactory. Gilutongan Island is one of the many off-grid islands in the Philippines with very limited access to electricity. Residents are provided with electricity from 6:00 p.m. to 10:30 p.m. through a 194-kVA diesel generator, paying US$ 0.14 per bulb and US$ 0.16 per outlet. Payment for electricity is collected on a daily basis with collections usually amounting to US$ 74.32 per day. With consumption totalling to 276 kW for 4.5 h, this roughly translates to a cost of US$ 1.21 per kWh. Using Hybrid Optimisation Model for Electric Renewables (HOMER), this paper presents a techno-economic analysis of a proposed cost-effective power generation system for the island, aiming to provide electricity access to the residents 24 h a day with reduced energy cost. Two options are considered: diesel-solar hybrid and solar only. Considering location constraints of the island, the hybrid system proves to be more effective, reducing cost of energy by 70% to US$ 0.3556 per kWh. Determining the load profile of the island is imperative in creating the system, dictating its size and capacity, which in turn affects its sustainability.